Large‐scale trade‐off between agricultural intensification and crop pollination services. Issue 4 (1st May 2014) - Deguines, Nicolas; Jono, Clémentine; Baude, Mathilde; Henry, Mickaël; Julliard, Romain; Fontaine, Colin
Abstract : Unprecedented growth in human populations has required the intensification of agriculture to enhance crop productivity, but this was achieved at a major cost to biodiversity. There is abundant local‐scale evidence that both pollinator diversity and pollination services decrease with increasing agricultural intensification. This raises concerns regarding food security, as two‐thirds of the world's major food crops are pollinator‐dependent. Whether such local findings scale up and affect crop production over larger scales is still being debated. Here, we analyzed a country‐wide dataset of the 54 major crops in France produced over the past two decades and found that benefits of agricultural intensification decrease with increasing pollinator dependence, to the extent that intensification failed to increase the yield of pollinator‐dependent crops and decreased the stability of their yield over time. This indicates that benefits from agricultural intensification may be offset by reductions in pollination services, and supports the need for an ecological intensification of agriculture through optimization of ecosystem services.